(untitled) (International Journal of Engineering and Computer Science, 2017)
ArgoUML is an UML diagramming application written in Java and released under the open source Eclipse Public License. By virtue of being a Java application, it is available on any platform supported by Java. Within the open-source community, ArgoUML represents a major cooperative effort for the development of a UML development environment, ArgoUML is still under development, and processing errors arise periodically.